Peran Guru dalam Meningkatkan Akhlak Siswa dengan Implementasi Al-Qur’an Siswa Kelas X di Pondok Modern Al-Azhar Muncar - Sipayung, Aghsal Azrial Akbar; Rahman, Fawait Syaiful; Purwanto, Anang Joko (MUNAQASYAH : Jurnal Ilmu Pendidikan dan Pembelajaran, 2023)
The role of teachers is very important in the world and has an influence on their students, so with that teachers are able to improve the morals of their students with the implementation of the Qur'an. This study aims to describe the role of teachers in improving the morals of class X students at Al Azhar Muncar Superior High School through the implementation of the Qur'an. This study uses a qualitative method with a case study approach. The research method that the researcher uses a qualitative method of case study type with in-depth interviev data collection techniques, interviews, and observations. The results of the study show that teachers have a very important role in improving students' morals. These roles include: (1) as a model or role model, (2) as an advisor to learning the Qur'an, (3) motivator, and (4) evaluator. The implementation of the Qur'an in learning is not only limited to memorization, but also an understanding of its meaning and application in daily life. This research has implications for teachers, schools, and the development of Islamic religious education curriculum. This research aims to find out how the implementation of the Qur'an in learning can improve the morals of class X students at the Al Azhar Muncar Superior High School. The results of the study show that the effective implementation of the Qur'an can improve students' morals through various activities, such as tahfidz, tafsir, and muhadatsah. Teachers as teachers have a central role in creating a learning environment that is conducive to the internalization of Qur'an values. This study concludes that holistic learning of the Qur'an can be a solution in overcoming students' moral problems